Political Movement of Islamic Religious Groups and Its Potential Conflict: A Study on Salafi in Pontianak, West Kalimantan, Indonesia - Hendry Ar., Eka (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2024)
The political movement of Salafi in the form of the da’wah movement has the potential for horizontal conflict. The potential for conflict in this movement was caused by the tend of “attacking” of this movement toward traditional religious groups. This research is located in Pontianak City West Kalimantan and uses qualitative methods and field research. The data was analyzed using the Islamist theory. The findings of this research are: First, the Salafi Islamic movement is a da’wah movement. The Manhaj Salafi (the Salafi Way) carries out tarbiyah and economic activities. Second, the Manhaj Salafi developed in Pontianak City is an apolitical manhaj and is not a Jihadist Salafi. Third, the responses of outsider groups are diverse, but prejudice is still strong against Salafi Islam, primarily related to the doctrine and its da’wah approach. Fourth, escalation towards violence and conflicts has not been observed, but there is an escalation. Based on the rising conflict potential, it is needed the anticipation to prevent the violence of the conflict between the Salafi movement and the traditional religious groups.